Identifying Accident Severity Factor On Surabaya Secondary Arterial Roads - Ahmad Utanaka; Wahyu Satyaning Budhi (NAROTAMA UNIVERSITY, Indonesia, 2022)
One of the CBD (Central Business District) areas of Surabaya is located at the center of the city, which is also known as the CBD Tunjungan area. CBD Tunjungan area is a hub for trade and services and has important accessibility which is surrounded by secondary arterial roads. Some secondary arterial roads which have access and high mobility to the CBD Tunjungan Area are Darmo Raya Road, Urip Sumoharjo Road and Basuki Rahmat Road. The high activity and mobility in the CBD area cause several transportation problems, one example is traffic accidents. The traffic accident data by the Directorate of Traffic and City Resort Police of Surabaya show that there are quite a several traffic accidents on these two roads. Traffic accidents are divided into three levels of severity i.e. slight, serious, and fatal injuries. To obtain the probability model of traffic accidents within every accident severity, it is necessary to do an analysis using the multinomial logistic regression method. The independent variables such as vehicle speed, lane width, accident time, and accident type, are considered to affect the equation model. Thus, it can be discovered the variables that affect the probability at the three levels of traffic accident severity.